Controls on light upper ocean waters entering the deep ocean ... - Vermeulen, Dennis; Gelderloos, Renske; Katsman, Caroline (4TU.ResearchData, 2025)
Data and code belonging to the PhD thesis of Dennis Vermeulen, Delft University of Technology, the Netherlands. ...